Pengaruh Iklim Organisasi, Keterlibatan Kerja dan Komitmen Afektif terhadap Kinerja Karyawan: - Riky Artya Setiawan; Prayekti Prayekti; Epsilandri Septyarini (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The purpose of this study was to determine the effect of organizational climate, work involvement, and affective commitment on employee performance. The population in this study were all employees of CV. Bhakti Astawira Sejahtera, totaling 50 people. The sampling technique used a saturated sample. The data analysis technique uses multiple linear regression. The results of the study show that there is an influence of Organizational Climate, Work Involvement, and Affective Commitment together or simultaneously have a significant positive effect on Employee Performance. Keywords: Organizational Climate, Work Engagement, Affective Commitment, Performance Employee